Faktor-faktor yang memengaruhi ibu dalam pemberian makanan tambahan pada anak bawah dua tahun (Baduta) - Silitonga, Angelienne Maria Prayscyllia; Fajar, Nur Alam; Kusumaningrum, Arie; Saci, Muhammad Amin Arigo (Holistik Jurnal Kesehatan, 2025)
Background: Toddlers (under two years old) are the first 1000 days of life, which is the period that begins from the formation of the fetus until the child is 2 years old. This period is the most important period in the growth and development period as an individual who will continue the nation and is expected to produce a reliable generation in competition in the global arena. To produce a reliable generation during this period, good growth and development stimulation is needed. Growth and development stimulation in the form of providing adequate nutrition and growth and development stimulation carried out by parents. Purpose: To analyze the factors that influence mothers in providing additional food to children under two years of age (toddlers). Method: Quantitative research with cross-sectional design. The population in this study were all mothers who had babies aged 6-24 months in Banyuasin Regency. In determining the sample of this study, the formula used was the Lemeshow formula with sampling using a simple random sampling technique. The independent variables in this study include; age, education, occupation, number of children in the family, and income, while the dependent variable is the provision of additional food. Data collection was carried out using a questionnaire method that was distributed directly to respondents. Data analysis carried out in this study used univariate analysis and bivariate analysis of the chi-square statistical test. Results: Based on the characteristics of the respondents' age, they are in the range of 20-34 years, as many as 57 respondents (53.8%) with a p value of 0.069 (>0.05). In general, respondents are included in the higher education category as many as 69 respondents (65.1%) with a p value of 0.010. Most respondents have a good level of knowledge as many as 65 respondents (61.3%) with a p value of 0.000 (<0.05). Almost all respondents are unemployed as many as 89 respondents (84.0%) with the results of the statistical test analysis showing a p value of 0.006. Most families have children >2 as many as 60 respondents (56.6%) with a p value of 0.000. Furthermore, most respondents' income < regional minimum wage as many as 73 respondents (68.9%) obtained a p value of 0.001 (<0.05). The variables of education, knowledge, occupation, number of children in the family, and parental income have a significant relationship to the provision of additional food. Meanwhile, there is one variable, namely age, which does not have a significant influence. Conclusion: The variables of education, knowledge, work, number of children in the family, and parental income have an effect on the provision of additional food with a p value <0.05. Meanwhile, the age variable does not significantly affect the provision of additional food in children under two years old.   Keywords: Additional Food; Mother; Under Two Years (Toddlers).   Pendahuluan: Baduta (bawah dua tahun) merupakan 1000 hari pertama kehidupan merupakan periode mulai dari janin terbentuk sampai nak berusia 2 tahun. Pada periode ini merupakan periode terpenting pada masa pertumbuhan dan perkembangan sebagai individu penerus bangsa yang dapat diharapakan untuk mencetak generasi yang handal dalam persaingan di kancah global. Agar menghasilkan genarasi yang handal pada periode tersebut memerlukan stimulasi pertumbuhan dan perkembangan yang baik. Stimulasi pertumbuhan berupa pemberian gizi yang adekuat dan stimulasi perkembangan yang dilakukan oleh orang tua. Tujuan: Untuk menganalisis faktor-faktor yang memengaruhi ibu dalam pemberian makanan tambahan pada anak bawah dua tahun (Baduta). Metode: Penelitian kuantitatif dengan rancangan cross-sectional. Populasi dalam penelitian ini adalah seluruh ibu yang memiliki bayi usia 6-24 bulan di wilayah Kabupaten Banyuasin. Dalam penentuan sampel penelitian ini, rumus yang digunakan adalah rumus Lemeshow dengan pengambilan sampel menggunakan teknik simple random sampling. Variabel independen dalam penelitian ini meliputi; umur, pendidikan, pekerjaan, jumlah anak dalam keluarga, dan pendapatan, sedangkan variabel dependennya adalah pemberian makanan tambahan. Pengumpulan data dilakukan dengan metode angket yang dibagi langsung ke responden. Analisis data yang dilakukan dalam penelitian menggunakan analisis univariat dan analisis bivariate uji statistic chi-square. Hasil: Berdasarkan karakteristik usia responden berada pada kisaran 20-34 sebanyak 57 responden (53.8%) dengan nilai p 0.069 (>0.05). Secara umum, responden masuk dalam kategori pendidikan tinggi sebanyak 69 (65.1%) dengan nilai p 0.010. Mayoritas responden memiliki tingkat pengetahuan baik sebanyak 65 (61.3%) dengan nilai p sebesar 0.000 (<0.05). Hampir seluruh responden tidak bekerja sebanyak 89 (84.0%) dengan hasil analisis uji statistik menunjukkan nilai p 0.006. Sebagian besar dalam satu keluarga memiliki jumlah anak >2 anak sebanyak 60 (56.6%) dengan nilai p 0.000. Selanjutnya mayoritas pendapatan responden < UMR sebanyak 73 (68.9%) diperoleh nilai p 0.001 (<0.05). Variabel pendidikan, pengetahuan, pekerjaan, jumlah anak dalam keluarga, dan pendapatan orangtua memiliki hubungan yang signifikan terhadap pemberian makanan tambahan. Sementara, terdapat satu variabel yaitu umur tidak berpengaruh secara signifikan. Simpulan: Variabel pendidikan, pengetahuan, pekerjaan, jumlah anak dalam keluarga, dan pendapatan orang tua berpengaruh terhadap pemberian makanan tambahan dengan perolehan p-value < 0.05. Sementara itu, variabel umur tidak berpengaruh secara signifikan terhadap pemberian makanan tambahan pada anak bawah dua tahun.   Kata Kunci: Anak Bawah Dua Tahun (Baduta); Ibu; Pemberian Makanan Tambahan.